2006
DOI: 10.1007/s10764-005-9008-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Impacts of Raptor Predation on Lemurs in Southeastern Madagascar

Abstract: I calculated rates of predation by 2 species of diurnal raptors, Polyboroides radiatus and Accipiter henstii, on the lemur community of Ranomafana National Park, Madagascar from 2700 h of observation and 470 prey deliveries at 7 nests of each hawk species. The 2 hawks consumed 7 of 12 lemurs found in the park region, with a body mass of 63-3500 g and including diurnal and nocturnal species of all group sizes. Calculations of predation rates indicate that raptor predation is a significant cause of mortality for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Polyandrous matings by females therefore only rarely compromise the dominant male's reproductive success, unlike in spotted hyenas, for example (Engh et al 2002), and may be part of females' reproductive tactics to maximize their fitness (Fisher et al 2006;Hoffman et al 2007). Theoretically, female sifakas could benefit from the presence of multiple males, e.g., in the form of improved mate choice, reduced vigilance (van Schaik and Hörstermann 1994), and predator mobbing (Karpanty 2006), as well as reduced takeover risk, as has been suggested for other lemurs (Ostner and Kappeler 2004). However, subordinate males apparently do not benefit directly from these potential services, as suggested by increased mortality rates in larger groups (Kappeler, unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…Polyandrous matings by females therefore only rarely compromise the dominant male's reproductive success, unlike in spotted hyenas, for example (Engh et al 2002), and may be part of females' reproductive tactics to maximize their fitness (Fisher et al 2006;Hoffman et al 2007). Theoretically, female sifakas could benefit from the presence of multiple males, e.g., in the form of improved mate choice, reduced vigilance (van Schaik and Hörstermann 1994), and predator mobbing (Karpanty 2006), as well as reduced takeover risk, as has been suggested for other lemurs (Ostner and Kappeler 2004). However, subordinate males apparently do not benefit directly from these potential services, as suggested by increased mortality rates in larger groups (Kappeler, unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, we used this daily proportional value as a proxy of risk from aerial predators since the littoral area mostly consists of evergreen trees with little seasonal leaf abscission (Bollen and Donati 2005 (Karpanty 2006;Karpanty and Wright 2007). Given the various hunting strategies of these raptors (Brockman 2003) and that playback experiments of aerial predators have shown Hapalemur to descend in the canopy in response to raptor calls (Karpanty and Wright 2007), we considered our canopy exposure method as an acceptable proxy as they should theoretically try to minimize the amount of time they are exposed from above.…”
Section: Behavioural Datamentioning
confidence: 99%
“…For the first search theme, 'dietary composition', 10 papers met the initial inclusion criteria, but of these 2 were not relevant to our review [Jolly et al, 2000;Kappel et al, 2011] and 2 were only suspected cases of predation [Curtis et al, 1999;Brockman et al, 2008], leaving 6 data papers. From the 'nocturnality' search, 4 of the 12 papers retained after reading the text reported sus-pected, rather than confirmed, events [Curtis et al, 1999, duplicated from diet search; Nekaris, 2001;Hilgartner et al, 2008;Rahlfs and Fichtel, 2010], 2 had primary data that were superceded in other articles included in the review [Gursky, 2002;Karpanty, 2006], 1 did not report species [Ray, 1997] and 1 reported a failed predation event [Eberle and Kappeler, 2008], to leave only 4 data papers. This totals 10 papers included in our review (6 resulting from the 'dietary composition' search and 4 from the 'nocturnality' search) and 2 book chapters.…”
Section: Literature Availablementioning
confidence: 99%